Evaluation of bond performance of corroded steel bars in concrete after high temperature exposure. (1st November 2019) - Zhang, Bai; Zhu, Hong; Chen, Jun; Yang, Ou
Highlights: Bond performance between corroded steel bars and concrete after high temperature exposure were investigated. Slight reinforcement corrosion could delay the bond behavior degradation caused by the elevated temperatures. The corrosion-induced cracks reduced the confinement of concrete cover and accelerated the deterioration of bond behavior. A bond-slip constitutive equation between corroded rebar and concrete after high temperature was proposed. Abstract: Pull-out tests were performed to study the deterioration of bond performance between concrete and corroded steel bars with designed corrosion levels of 0%, 1.0%, 2.0%, 4.0%, and 6.0% after the specimens were exposed to 20, 200, 400, 600, and 800 °C. The experimental results indicated that the deterioration of bond performance, including the bond strength, bond stiffness, bond energy dissipation, and residual bond stress, were influenced by the reinforcement corrosion and temperature exposure. The rate and severity of bond degradation after temperature exposure for corroded specimens, especially those specimens with corrosion-induced cracks, were more pronounced than those of the uncorroded specimens. An empirical model of bond strength and a simplified bond-slip constitutive equation that considers the influence of reinforcement corrosion and temperature exposure were proposed, and the practicability of the suggested model was verified by experimental data from other researchers.